I am studying the fermionic hopping model on a one-dimensional chain with $N$ sites and lattice constant $1$: $$ H=\sum_\ell c_{\ell}^\dagger c_{\ell+1}+c_{\ell+1}^\dagger c_\ell. $$ This is usually done by diagonalizing $H$ with the help of a Fourier transform. In the course of the calculation, the identity $$ \frac{1}{N}\sum_\ell e^{i\ell(k-k^\prime)}=\delta_{k,k^\prime} $$ is used. I was now wondering where this identity comes from. I followed the computation of Scalettar where the identity is listed on page 11.


1 Answer 1


The identity you are talking about is : $$\frac{1}{N}\sum_{l=1}^{N}e_{}^{il(k-k')}=\delta_{kk'}^{}$$ with $k=\frac{2\pi n}{N}$ and $k'=\frac{2\pi n'}{N}$for some $n,n' \in \{1,\dots,N\}$. To see it note : $$\sum_{k=0}^{N-1}x^{k}_{}=\frac{1-x_{}^{N}}{1-x}.$$ Use it to proove.

$\textbf{Proof :}$

For $k=k'$ : Clearly $\frac{1}{N}\sum_{l=1}^{N}e_{}^{il(k-k')}=\frac{1}{N}\sum_{l=1}^{N} 1 =1.$

For $k \neq k'$ : $\frac{1}{N}\sum_{l=1}^{N}e_{}^{il(k-k')}=\frac{e^{i\frac{2\pi}{N}(n-n')}}{N}\sum_{l=0}^{N-1} e^{il\frac{2\pi}{N}(n-n')} = \frac{e^{i\frac{2\pi}{N}(n-n')}}{N}\frac{1-e^{i2\pi(n-n')}}{1-e^{i\frac{2\pi}{N}(n-n')}}=\frac{e^{i\frac{2\pi}{N}(n-n')}}{N}\frac{1-1}{1-e^{i\frac{2\pi}{N}(n-n')}}=0.$

Hence :$$\mathbf{\frac{1}{N}\sum_{l=1}^{N}e_{}^{il(k-k')}=\delta_{kk'}^{}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.